1989
DOI: 10.1111/j.1755-3768.1989.tb07110.x
|View full text |Cite
|
Sign up to set email alerts
|

Lectin receptors of normal and dystrophic corneas

Abstract: In recent years, our laboratory has used lectins to detect carbohydrate-related abnormalities in dystrophic corneas and species-specific differences in the carbohydrates of normal corneas. These studies have: 1) demonstrated that abnormal glycoconjugates are present in corneas with macular and lattice dystrophy, 2) provided additional means of differentiating corneas with macular, lattice and granular dystrophy, 3) demonstrated that distinct species-specific differences are present in the glycoconjugates of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
5
3
2
Order By: Relevance
“…Lectin binding to the cornea in different species, e.g. calf has been studied previously by Panjwani and Baum, 1989. The results of this study are generally in accordance with their findings but there are also some differences: Panjwani and Baum, 1989 mentioned that Con A and PNA binds to the apical corneal epithelium, whereas in my results show that Con A binds throughout all epithelial layers of the cornea.…”
Section: Discussionsupporting
confidence: 89%
“…Lectin binding to the cornea in different species, e.g. calf has been studied previously by Panjwani and Baum, 1989. The results of this study are generally in accordance with their findings but there are also some differences: Panjwani and Baum, 1989 mentioned that Con A and PNA binds to the apical corneal epithelium, whereas in my results show that Con A binds throughout all epithelial layers of the cornea.…”
Section: Discussionsupporting
confidence: 89%
“…calf, has been studied previously by Panjwani and Baum, 1989. 16 The results of this study are generally in accordance with their findings but there are also some differences.…”
Section: Discussionsupporting
confidence: 81%
“…calf, has been studied previously by Panjwani and Baum, 1989. 16 The results of this study are generally in accordance with their findings but there are also some differences. Panjwani and Baum, 10 mentioned that Con A and PNA were bound to the corneal epithelium, whereas our results showed that Con A was bound throughout all epithelial layers of the cornea.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations